THE IMPLEMENTATION OF PROJECT-BASED LEARNING TO ENHANCE STUDENTS' READING COMPREHENSION - Andriansah, Fajar; Fitriyani, Peny; Fadloeli, Odo (PROJECT (Professional Journal of English Education), 2019)
English is one of the students’ needs to learn. In English there is an important skill that must be mastered that is reading comprehension. Without that, students’ have difficulties in understanding the text, especially narrative text. The researcher conducting Classroom Action Research (CAR) design. The researcher used quantitative and qualitative data were collected. Quantitative data relates to the students’ reading scores in pre-test and post-test. Qualitative data concerns with any occasions and changes happening during classroom activities. The purpose of the research was to figure out whether there is any significant improvement in the students' reading comprehension after being taught by implementing project-based learning. The sample of the research is XI RPL in Vocational High School that consisted of 34 students. The result indicates that the students' reading comprehension of narrative text by using PBL has increased. The improvement covers two points, they are (1) Improvement on students’ mean score. Mean score of pretests was 60.32. score of posttests 1 was 74.19. Which the average score of posttests 2 was 87.42, (2) Students’ reading comprehension was improved. It can be accomplished that there is a significant enhance in the students' achievement after they were taught by project-based learning.